Cross-Subsidization in Institutional Asset Management Firms - Chaudhuri, Ranadeb; Ivković, Zoran; Trzcinka, Charles (Review of Financial Studies, 2018)
We study cross-subsidization among U.S. equity products managed by institutional asset management firms. We find returns-based evidence consistent with both cross-subsidization receipt by strong recent performers that are relatively small in their firms and provision by products that are relatively large in their firms. Tax-exempt investors and taxable investors do not have a clear ranking by expertise, but tax-exempt investors’ agency issues are more complex. Accordingly, taxable clients have more flow-performance nonlinearity and receive more (and provide less) cross-subsidization. Taxable investor flows appear more discerning, but only under the circumstances conducive to cross-subsidization, suggesting that “more discerning” likely means “more cross-subsidized.”Received May 11, 2015; editorial decision April 22, 2017 by Editor Andrew Karolyi.